Correlation between Parenting Styles and Peer Attachment with Aggressive Behavior Potentials in Adolescent Boys - Yunias Setiawati1, Kusufia Mirantri1, H. J. Mukono2, Joni Wahyuhadu3, Endang Warsiki1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Adolescence is a transitional phase that causes biological, cognitive, social-emotional, and behavioral changes. One of the issues of concern is aggressive behavior in adolescents. Parenting styles and peer attachment are one of the factors that have an influence on potential aggressive behavior in adolescent boys. Objectives To analyze the relationship between parenting styles and peer attachment to the potential aggressive behavior of adolescent boys. Method: The subjects were junior high school male students who are cared for by both biological parents and can follow all of the research procedures. The research design was cross-sectional with total sampling technique. Subjects performed anamnesis related data self, parent demographic data, and peers. (PAQ), (IPPA) (BPAQ). The analyzes used were Pearson, Spearman, and Anova. Results: The majority of parenting styles was permissive (34.06%; 48.00%). Parenting styles and peer attachments did not have a significant relationship with potential aggressive behavior (p = 0.798; p = 0.071; p = 0.695). There was a negative correlation of peer attachment with alienation dimension (p = 0.001). Other significant dimensions with potential dimensions of aggressive behavior were trust (p = 0.018; 0.022) and communication (p = 0.029; p = 0.000). Conclusion: Parenting styles and peer attachments did not have a meaningful relationship with potential aggressive behavior in adolescent boys. However, there were some significant correlations between the dimensions of parenting and peer attachment with potential dimensions of aggressive behavior.